The Effects of Wordle Media on Students’ Vocabulary Mastery - Nailul Author Restu Pamungkas (JETAL: Journal of English Teaching & Applied Linguistic, 2021)
The incorporation of technology-based media and teaching English vocabulary is considered to be puzzling. Teachers should take into account the students’ learning style and their capabilities in operating the technology-based media. One of the practical technology-based media to teach vocabulary is Wordle. This study attempted to examine the effectiveness of an intervention using Wordle media to improve students’ vocabulary mastery. This study involved 74 students of a private vocational school in Bandung. A quasi experimental research study was employed as the design of research. The findings indicated that implementing Wordle media proves to be effective in enhancing the students’ vocabulary mastery. There is significance differences between experimental and control classes.